2021
DOI: 10.1002/jcsm.12831
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography‐defined low skeletal muscle index and density in cancer patients: observations from a systematic review

Abstract: Background Computed tomography (CT) analysis of body composition has garnered interest as a potential prognostic tool in those with cancer. A range of pre‐defined thresholds currently exist within the literature to define low skeletal muscle mass and density. The aim of the present systematic review was to assess the prevalence of low skeletal muscle index (SMI) and density (SMD) within the literature, across a range of common solid tumours. Methods A systematic search of PubMed was carried out to identify stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 66 publications
(122 reference statements)
8
82
0
6
Order By: Relevance
“…CT body composition parameters at L3 have been found to be of predictive value in many entities including COVID-19 9 , 10 , 14 . However, most COVID-19 patients only receive chest X-rays or thoracic CT scans and while there are reviews with hundreds of studies on abdominal CT body composition measurements 15 , 16 experience on thoracic CT body composition parameters is less profound, with especially few studies on thoracic CT body composition assessment in COVID-19 5 , 6 , 17 . Furthermore, no consensus exists on which thoracic muscle groups to employ and proposed thoracic cut-off values to assess sarcopenia vary 18 21 .…”
Section: Introductionmentioning
confidence: 99%
“…CT body composition parameters at L3 have been found to be of predictive value in many entities including COVID-19 9 , 10 , 14 . However, most COVID-19 patients only receive chest X-rays or thoracic CT scans and while there are reviews with hundreds of studies on abdominal CT body composition measurements 15 , 16 experience on thoracic CT body composition parameters is less profound, with especially few studies on thoracic CT body composition assessment in COVID-19 5 , 6 , 17 . Furthermore, no consensus exists on which thoracic muscle groups to employ and proposed thoracic cut-off values to assess sarcopenia vary 18 21 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Skeletal muscle mass is most often calculated from the cumulative volume of the intra-abdominal musculature on a CT image slice, generally at the level of the third lumbar vertebra, normalized by the square of the patient's height in metres (skeletal muscle index, SMI), analogous to that of BMI. 6 Indeed, CT-derived muscle mass measurements have been shown to be consistent with measurements of other modalities, 7 specifically bioelectrical impedance analysis 8 and dual-energy X-ray absorptiometry. 9 Skeletal muscle density (SMD) on the other hand is an assessment of muscle quality, with striated skeletal muscle, free from fat infiltration, having a greater density on CT analysis compared against that with fat deposition.…”
Section: Introductionmentioning
confidence: 73%
“…As such, the present observations are in keeping with those of a recent review by our group, of 160 studies of CT-derived SMI and SMD that found poor muscle status was endemic in patients with cancer, suggesting that tumour stage was not a major determinant of sarcopenia. 6 Furthermore, in the review we also hypothesized that the prognostic value of sarcopenia may reflect its measure of the nutritional and functional reserve of the cancer patient and that it is imperative that such body composition measurements be used in conjunction with potential confounding factors such as systemic inflammation. 6 Hacker and co-workers reported similar observations in a recent longitudinal study of patients with advanced gastric and oesophagogastric junctional cancer.…”
Section: Table 4amentioning
confidence: 99%
“…Раніше було доведено, що площа поперечного зрізу скелетних м'язів на рівні L3 тісно корелює з загальною масою скелетних м'язів [25] та, на відміну від м'язів кінцівок, не залежить від фізичної активності [7]. Індекс скелетних м'язів (Skeletal Muscle Index, SMI), що являє собою скориговану до зросту площу поперечного зрізу скелетних м'язів на рівні L3, є найбільш дослідженим показником м'язової маси у пацієнтів з онкопатологією, термінальними захворюваннями печінки та показав свою вагому прогностичну цінність [19,20,22,24]. Альтернативним місцем оцінки загальної м'язової маси є поперековий м'яз, який легко ідентифікується на КТ та може бути точно окреслений.…”
Section: вступunclassified